1999
DOI: 10.1007/s004649900901
|View full text |Cite
|
Sign up to set email alerts
|

The fate of the dropped gallstones during laparoscopic cholecystectomy

Abstract: Stones can be spilled from the gallbladder during laparoscopic cholecystectomy. These stones can be left in the peritoneal cavity or trapped at the trocar site. The potential late sequel and associated morbidity are not well documented. We reviewed the records of four patients who underwent laparoscopic cholecystectomy at Mount Sinai Medical Center in New York City who suffered from late complications attributed to gallstones left in the peritoneal cavity or abdominal wall. Four patients presented 1-14 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Stones removal will usually involve open surgery [39,45,56,58]; however, laparoscopic [26] and thorascopic [3] techniques are occasionally successful in retrieving stones. Percutaneous techniques have also been used to remove stones from subphrenic collections [54] and sinus tracts [33].…”
Section: Management Of Late Complicationsmentioning
confidence: 99%
“…Stones removal will usually involve open surgery [39,45,56,58]; however, laparoscopic [26] and thorascopic [3] techniques are occasionally successful in retrieving stones. Percutaneous techniques have also been used to remove stones from subphrenic collections [54] and sinus tracts [33].…”
Section: Management Of Late Complicationsmentioning
confidence: 99%
“…It has also been suggested that conversion should be considered if a large number of unretrieved stones are split. 33,34,37 Mortality in LC is reported to be less than that in OC. 3 In a review of 114,005 cases from the US, an overall related mortality of 0.06% was reported.…”
Section: Discussionmentioning
confidence: 98%
“…Cases of lost stones have been reported in up to 40% of LC, 32 but only about 0.08% develop stone-related clinical problems, 33 which include intraperitoneal abscess, cutaneous umbilical sinus, systemic infection, fibrosis, adhesions, fistulas and migration to other sides. [32][33][34][35][36][37][38] We had no problems with the 3.3% missed stones. In OC, it is less of a problem because they can be retrieved more easily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports, like Brueggemeyer et al, 12 demonstrated that spillage of gallstones can cause intra peritoneal abscess. Zamir et al 13 reported similar findings.…”
Section: Discussionmentioning
confidence: 99%